The Mason jar cookbook : 80 healthy and portable meals - Fazio, Amy (Skyhorse Publishing, 2016)
Amy Fazio's second book, The Mason Jar Cookbook, shows the versatility and convenience of creating dishes in the mason jar. No longer just for jellies and jam, mason jars are now being filled in the most creative and often super-healthy ways, such as with salads and casseroles. The easy-to-follow recipes in this book will show you how to prepare breakfast, lunch, and dinner in a mason jar. Dessert too.--Publisher's description.